Heart rate variability in response to the recall of attachment memories. Issue 6 (1st November 2020) - Zingaretti, Pietro; Giovanardi, Guido; Cruciani, Gianluca; Lingiardi, Vittorio; Ottaviani, Cristina; Spitoni, Grazia Fernanda
ABSTRACT: Internal Working Models of the attachment system modulate emotional responses and the Disorganized attachment pattern is characterized by the breakdown of such regulation. Vagally-mediated heart rate variability (vmHRV) is an index of flexible emotional responding. This study investigated vmHRV in non-clinical adults with an Organized or Disorganized attachment pattern before, during, and after the recall of attachment memories via the Adult Attachment Interview (AAI). Whereas the Organized group exhibited a typical decrease in vmHRV during the AAI and asubsequent return to a baseline-like pattern, the Disorganized group unexpectedly showed a sustained increase in vmHRV during the AAI which also persisted during the recovery phase. Results suggest that while Organized face the recollection of attachment memories by showing the adaptive stress response characterized by parasympathetic withdrawal and immediate recovery, individuals with Disorganized attachment need to keep regulating their emotions effortfully both during and after the recall of potential traumatic events.